A sustainable afterlife for post-industrial sites: balancing conservation, regeneration and heritage tourism. Issue 3 (4th March 2023) - Della Lucia, Maria; Pashkevich, Albina
ABSTRACT: Giving industrial sites new life requires enabling change and overcoming change resistance. By cross-fertilizing relevant managerial and urban development literature, this study develops a theoretical and analytical framework that integrates several factors that can lead to the sustainable transformation of post-industrial sites. Case evidence collected using qualitative methods at the Great Copper Mountain WHS, Sweden, reveals a Managerial innovation model of industrial heritage regeneration which fails to fully engage the surrounding communities. This model is associated with early-stage post-industrial heritage tourism. The resistance, controversy and community misperceptions hindering the adaptive reuse of the site's industrial heritage and urban surrounds are mainly determined by institutional norms arising from the industrial monoculture. Change management entails working to dismantle lock-ins and empower change at different levels.